Carbon cloth loaded iron oxide material as well as preparation method and application thereof

By loading iron tetroxide nanoparticles on carbon cloth carbon fibers and generating porous Co-MOFs to form a three-dimensional structure of carbon cloth @Fe3O4@Co-MOFs, the problems of poor conductivity and unstable circulation performance of iron oxide materials are solved, and a high capacity and stable lithium-ion battery negative electrode material is achieved.

CN119890274AActive Publication Date: 2025-04-25NANJING UNIV OF POSTS & TELECOMM
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510263342.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-25
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode material iron oxide materials have problems such as poor conductivity and unstable circulation performance, which is difficult to meet the needs of high capacity, stability and safety.

Method used

Using the preparation method of carbon cloth-loaded iron oxide material, a three-dimensional structure of carbon cloth @Fe3O4@Co-MOFs are formed by uniformly growing iron tetroxide nanoparticles on carbon cloth carbon fibers, and a cobalt metal organic frame (Co-MOFs) with a porous structure is formed on their surface.

Benefits of technology

It improves the conductivity and mechanical stability of iron oxide composite materials, enhances electrochemical performance and cyclic stability, and is suitable for negative electrode materials for high-capacity lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890274A_ABST
    Figure CN119890274A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon cloth loaded iron oxide material, which comprises the following steps: soaking carbon cloth in a nitric acid solution, taking out, cleaning and drying to obtain pretreated carbon cloth; adding ferric chloride hexahydrate and sodium acetate into ethylene glycol, stirring and dissolving to obtain a mixed solution, transferring the mixed solution into a stainless steel high-pressure kettle with a polytetrafluoroethylene lining, putting the pretreated carbon cloth, sealing, carrying out hydrothermal reaction at 170-190 DEG C, taking out and cleaning after the hydrothermal reaction is finished to obtain a precursor, soaking the precursor in a mixed solution of 2-methylimidazole and cobalt nitrate, and drying to obtain the cobalt-doped carbon cloth composite material. And taking out, cleaning, drying in vacuum, and finally calcining under the protection of argon, thereby obtaining the product. Compared with the prior art, the carbon cloth loaded iron oxide material has excellent conductivity, electrochemical performance and mechanical stability and is particularly suitable for being used as a lithium ion battery negative electrode, and a lithium battery assembled by using the carbon cloth loaded iron oxide material shows good cycling stability and rate capability and has a good application prospect in the aspect of lithium ion energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a carbon cloth loaded iron oxide material and a preparation method and application thereof. Background Art

[0002] In recent years, as the high-quality development of energy and environmentally friendly strategies in the new era have gradually gained popularity, lithium-ion battery technology has been widely used in human production and life, such as new energy electric vehicles, wearable electronic devices, etc. However, with the development of science and technology, people's demand for high-capacity, safe and reliable batteries is increasing. At present, the commonly used negative electrode material for lithium-ion batteries is graphite, but the theoretical capacity of graphite is low and cannot meet the growing demand for high capacity. Finding new materials with high capacity, stability and safety has become a research hotspot.

[0003] At present, the research on negative electrode materials for lithium-ion batteries is mainly focused on the following categories: carbon materials, transition metal oxides, Mxene, etc. Among them, iron oxide has attracted widespread attention due to its high theoretical capacity, low cost, and environmental friendliness. However, single iron oxide materials have poor conductivity, large volume expansion, and easy crushing during charging and discharging, resulting in unstable cycle performance. Therefore, how to improve the conductivity of iron oxide materials and the stability of cycle performance is a key technical problem that needs to be solved urgently. At present, there are two mainstream problem-solving ideas. One is to prepare iron oxide particles into various nanostructures, such as nanowires, nanorods, etc., to improve the stability of the material, reduce the stress during volume change, and improve stability. However, the preparation of electrodes under this method requires the addition of a binder, resulting in low conductivity; the other is to composite iron oxide and carbon materials. Carbon materials have excellent conductivity, which can improve the conductivity of composite materials and have a self-supporting structure, avoiding the addition of binders, but this method is not ideal for improving the stability of materials. Summary of the invention

[0004] The purpose of the present invention is to solve the above-mentioned deficiencies of the prior art and provide a method for preparing a carbon cloth-loaded iron oxide material. The prepared carbon cloth-loaded iron oxide material has excellent conductivity, electrochemical properties and mechanical stability.

[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0006] A method for preparing a carbon cloth-loaded iron oxide material comprises the following steps:

[0007] S1, soaking the carbon cloth in a nitric acid solution, taking it out, washing it and vacuum drying it to obtain a pretreated carbon cloth;

[0008] S2, adding ferric chloride hexahydrate and sodium acetate to ethylene glycol, stirring and dissolving to obtain a mixed solution, transferring the mixed solution into a stainless steel autoclave lined with polytetrafluoroethylene, placing the pretreated carbon cloth and sealing, and hydrothermally reacting at 170-190° C. for 10-16 hours, taking out after completion, and washing to obtain a precursor;

[0009] S3, soaking the precursor in a mixed solution of 2-methylimidazole and cobalt nitrate, taking it out after completion, cleaning it, vacuum drying it, and finally heating it to 400-600°C under argon protection for calcination to obtain a carbon cloth-loaded iron oxide material.

[0010] Furthermore, in step S1, the volume concentration of the nitric acid solution is 60%-70%.

[0011] Furthermore, in step S1, the cleaning is firstly ultrasonically cleaned with acetone for 90 minutes, and then cleaned with deionized water.

[0012] Furthermore, in step S1, the vacuum drying temperature is 80°C.

[0013] Furthermore, in step S2, the molar ratio of ferric chloride hexahydrate to sodium acetate is 1:(2-2.5).

[0014] Furthermore, in step S2, the temperature of the hydrothermal reaction is 180° C. and the time is 12 hours. Under this condition, the ferroferric oxide on the surface of the carbon fiber is evenly distributed without obvious agglomeration.

[0015] Furthermore, in step S3, the soaking temperature is 80-90°C and the soaking time is 10-15h.

[0016] Further, in step S3, in the mixed solution of 2-methylimidazole and cobalt nitrate, the concentration of 2-methylimidazole is 4-6 mol / L, and the concentration of cobalt nitrate is 1-2 mol / L.

[0017] Furthermore, in step S3, the heating rate is 5°C / min, the calcination temperature is 500°C, and the calcination time is 2h. Under these conditions, Co-MOFs has strong stability and a uniformly distributed porous structure.

[0018] The carbon cloth loaded iron oxide material prepared by the above method.

[0019] The carbon cloth loaded iron oxide material prepared by the above method is used in the preparation of negative electrodes for lithium-ion batteries.

[0020] Principle of the invention: The invention loads granular iron oxide active material on carbon cloth carbon fiber, greatly improving the conductivity of iron oxide negative electrode material, while avoiding the great limitation of uneven dispersion of active material and use of inactive ingredients such as adhesive, conductive agent (conductive carbon black) during electrode material coating, forming a self-supporting structure. In order to further improve the stability of iron oxide composite material, based on the design of carbon cloth @Fe3O4 composite material, a metal organic framework is grown on its surface. Metal-organic framework (MOFs) is formed by strong chemical bonds between metal cations and organic ligands, with high specific surface area and unique stability. The pores of MOFs material can be filled with electrolyte to enhance the diffusion of lithium ions and reduce the impedance of the battery, showing excellent performance in Li+ storage. Combining iron oxide material with metal organic framework on carbon cloth substrate to form a unique three-dimensional structure is an effective strategy to improve the electrochemical performance of LIB.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention discloses a method for preparing a carbon cloth-loaded iron oxide material. The prepared carbon cloth-loaded iron oxide material is a three-dimensional structure of carbon cloth@Fe3O4@Co-MOFs. In the carbon cloth-loaded iron oxide material, the mass percentage content of carbon cloth and cobalt metal organic framework is 89-90%, the mass percentage content of ferroferric oxide is 10-11%, and the ferroferric oxide particles are uniformly covered on the carbon fiber rods of the carbon cloth. The cobalt metal organic framework and the carbon fiber rods are both in micron size. The pore size of the cobalt metal organic framework is about 20nm, and the diameter of the carbon fiber rod is 10-12μm.

[0023] (2) The present invention uniformly grows and covers ferroferric oxide nanoparticles on carbon cloth carbon fiber rods, and generates Co-MOFs with a porous structure on the surface of the nanoparticles for encapsulation, while retaining the excellent conductivity of carbon fiber and the stability of Co-MOFs, exerting a synergistic effect, and improving the electrochemical performance and mechanical stability of the iron oxide composite material. The three-dimensional structure of the composite material is divided into three layers, the base is carbon fiber, and the upper layer is a porous structure, which together play the role of encapsulating active nanoparticles, so that the composite material can adapt to the volume change during the charge and discharge process and increase its mechanical properties. At the same time, the outer layer with a porous structure effectively reduces the diffusion distance of lithium ions and increases the contact area between the electrode and the electrolyte.

[0024] (3) The carbon cloth-loaded iron oxide material of the present invention is used as a lithium ion self-supporting flexible electrode, and the battery assembled with the carbon cloth@Fe3O4@Co-MOFs three-dimensional material as the negative electrode and the lithium sheet as the positive electrode shows good cycle stability and rate performance, and has great application prospects in the preparation of lithium ion energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The scanning electron microscope image and elemental analysis image of the carbon cloth loaded iron oxide material prepared in Example 1;

[0026] Figure 2 This is the XRD pattern of the carbon cloth-loaded iron oxide material prepared in Example 1;

[0027] Figure 3 This is a bet test diagram of the carbon cloth loaded iron oxide material prepared in Example 1;

[0028] Figure 4 This is a Raman spectrum of the carbon cloth-loaded iron oxide material prepared in Example 1;

[0029] Figure 5 This is an X-ray photoelectron spectrum of the carbon cloth-supported iron oxide material prepared in Example 1;

[0030] Figure 6 The electrochemical impedance spectrum of the carbon cloth-loaded iron oxide material prepared in Example 1;

[0031] Figure 7 The test results of the cycle performance of a lithium-ion battery assembled using the carbon cloth-supported iron oxide material prepared in Example 1 as the negative electrode at a current of 1 A / g;

[0032] Figure 8 The test results of the cycle performance of the lithium-ion battery assembled with the carbon cloth-supported iron oxide material prepared in Example 1 as the negative electrode at currents of 6A / g and 10A / g;

[0033] Fig. 9 The figure is a rate performance diagram of a lithium-ion battery assembled using the carbon cloth-loaded iron oxide material prepared in Example 1 as the negative electrode at different current densities. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings and specific embodiments.

[0035] Example 1

[0036] A method for preparing a carbon cloth-loaded iron oxide material comprises the following steps:

[0037] S1. Soak a 3 cm × 3 cm carbon cloth in a nitric acid solution with a volume concentration of 65%, take it out and ultrasonically clean it with acetone for 90 minutes, then clean it with deionized water, and vacuum dry it at 80° C. to obtain a pretreated carbon cloth;

[0038] S2. Add 20 mmol of ferric chloride hexahydrate and 44 mmol of sodium acetate to 60 mL of ethylene glycol, stir and dissolve to obtain a mixed solution, transfer the mixed solution into a stainless steel autoclave lined with polytetrafluoroethylene, put in the pretreated carbon cloth and seal it, hydrothermally react at 180°C for 12 hours, take it out after completion, wash it three times with deionized water, and obtain a precursor (carbon cloth @Fe3O4 precursor);

[0039] S3. The precursor was immersed in 80 mL of a mixed solution of 2-methylimidazole and cobalt nitrate (the concentration of 2-methylimidazole was 4 mol / L and the concentration of cobalt nitrate was 1.25 mol / L), and kept at 85 °C for 12 h. After the mixture was removed, it was washed with deionized water, and then dried at 60 °C in a vacuum oven. Finally, the mixture was heated to 500 °C at a rate of 5 °C / min and calcined for 2 h under argon protection to obtain a carbon cloth-loaded iron oxide material, i.e., carbon cloth@Fe3O4@Co-MOFs composite material.

[0040] Figure 1 The scanning electron microscope image and elemental analysis image of the carbon cloth-loaded iron oxide material prepared in Example 1, wherein: Figure 1 (a) is a scanning electron microscope image of carbon cloth loaded with iron oxide material. Figure 1 (b) is the HR-TEM image of carbon cloth-supported iron oxide material. Figure 1 (c)- Figure 1 (f) is the element mapping diagram of carbon cloth loaded iron oxide material. Figure 1 (a) It can be seen that the iron oxide nanoparticles are uniformly covered on the carbon fiber rods of the carbon cloth in the form of particles, and the cobalt metal organic framework is wrapped on the active particles in the form of porous thorns. The cobalt metal organic framework and the carbon fiber rods are both micron-sized. Figure 1 (b) It can be seen that the Co-MOFs with a porous shape are evenly distributed on the carbon fibers, and the ferroferric oxide particles are wrapped in them, which not only provides a good conductive network but also facilitates the transmission of electrons in the electrode material. Figure 1 (c)- Figure 1 (f) It can be seen that the element mapping image shows Fe (green), O (blue), C (red), and Co (purple) elements, and proves that Fe, O, C, and Co elements exist and are evenly distributed in the material.

[0041] Figure 2The XRD graph of the carbon cloth loaded iron oxide material prepared in Example 1 shows that, compared with the carbon cloth, the carbon cloth @ Fe3O4 precursor shows obvious diffraction peaks at 30.1°, 35.5° and 43.1°, confirming that after step S2, ferroferric oxide is successfully hydrothermally grown on the surface of the carbon cloth fiber. In the XRD spectrum of the carbon cloth @ Fe3O4 @ Co-MOFs composite material prepared in Example 1, the XRD peak of iron oxide is covered by the peak of Co-MOFs, indicating that Co-MOFs grow on the surface of the carbon cloth @ Fe3O4 precursor and encapsulate the ferroferric oxide nanoparticles, which can improve the stability of the material.

[0042] Figure 3 This is the bet test diagram of the carbon cloth loaded iron oxide material prepared in Example 1. It can be seen that the surface area of ​​the carbon cloth loaded iron oxide material is 42 cm 2 g -1 , the average pore size distribution is concentrated around 20nm.

[0043] Figure 4 This is the Raman spectrum of the carbon cloth-loaded iron oxide material prepared in Example 1, 1341 cm -1 The D band peak at 1577 cm-1 and the G band peak at 1577 cm-1 proved the formation of graphitic carbon layers, IG / ID=1.17.

[0044] Figure 5 This is the X-ray photoelectron spectrum of the carbon cloth-supported iron oxide material prepared in Example 1, wherein Figure 5 A is the full spectrum, Figure 5 B is the Co 2p diagram, Figure 5 C is the C1s graph, Figure 5 D is the O1s diagram, Figure 5 E is the Fe 2p diagram, Figure 5 F is the N1s graph, and the spectrum shows that the carbon cloth-loaded iron oxide material is composed of Co, Fe, N, O, C and other elements. Figure 5 A spectrum shows that Co 2+ The existence of fully proves that Co-MOFs are synthesized on carbon cloth@Fe3O4Co-MOFs. Figure 5 D and Figure 5 E demonstrated the successful synthesis of ferroferric oxide, combined with Figure 2 The results of the temperature-increasing XRD pattern further confirmed the successful preparation of carbon cloth-loaded iron oxide material (carbon cloth@Fe3O4@Co-MOFs).

[0045] Figure 6This is the electrochemical impedance spectrum (EIS) of the carbon cloth loaded iron oxide material prepared in Example 1. The semicircle in the figure reflects the resistance of the SEI layer and the transfer resistance between the electrode surface and the electrolyte. It can be seen that the semicircle diameter of the carbon cloth @Fe3O4@Co-MOFs composite material prepared in Example 1 is smaller than that of carbon cloth @Fe3O4 and Fe3O4, indicating that the charge transfer resistance is lower and the electronic performance is smaller. It proves that the three-dimensional structure can improve the conductivity of the material.

[0046] The carbon cloth loaded iron oxide material prepared in Example 1 was used to prepare a negative electrode of a lithium ion battery, and then assembled into a lithium ion battery, and the performance of the lithium ion battery was tested. The specific method is as follows:

[0047] 1) Lithium battery assembly: CR2032 coin-shaped batteries were used for electrochemical testing. The carbon cloth-loaded iron oxide material (carbon cloth@Fe3O4@Co-MOFs), carbon cloth@Fe3O4 precursor and Fe3O4 prepared in Example 1 were used as working electrodes (negative electrodes) respectively, and lithium foil was used as the counter electrode.

[0048] 2) The two electrodes were cut into discs with a diameter of 12 mm, Celgard 2400 was used as a separator, and 1 M LiPF6 was added to ethylene carbonate (EC) / diethyl carbonate (DEC) / dimethyl carbonate (DMC) (volume ratio of 1:1:1) as the electrolyte; the battery was assembled in an argon-filled glove box, and the H2O and O2 contents were kept below 0.1 ppm.

[0049] 3) Conduct battery performance tests on the assembled lithium-ion batteries.

[0050] Figure 7 The test results of the cycling performance of a lithium-ion battery assembled with the carbon cloth-loaded iron oxide material prepared in Example 1 as the negative electrode at a current of 1 A / g show that the capacity of the lithium-ion battery assembled with the carbon cloth@Fe3O4@Co-MOFs composite material prepared in Example 1 as the negative electrode has basically no capacity decay after 100 cycles at a current of 1 A / g, and has a higher specific capacity and very good cycling performance.

[0051] Figure 8 The test results of the cycle performance of the lithium-ion battery assembled with the carbon cloth-supported iron oxide material prepared in Example 1 as the negative electrode at currents of 6A / g and 10A / g are shown, wherein: Figure 8 (a) is the cycle performance test result at a current of 6 A / g, Figure 8 (b) is the cycling performance test result at a current of 10 A / g. It can be found that the battery still has a high capacity of 335 mAh g after 500 and 1000 cycles at a high current of 6 A / g and 10 A / g, respectively. -1 and 265mAh g-1 .

[0052] Fig. 9 The figure is a rate performance diagram of a lithium-ion battery assembled with the carbon cloth-loaded iron oxide material prepared in Example 1 as the negative electrode at different current densities. It can be seen that at current densities of 0.1A / g, 0.3A / g, 0.5A / g, 1A / g, 3A / g, 5A / g and 10A / g, the entire battery exhibits good rate performance, and the reversible capacities are 1626, 1689, 1695, 1549, 1129, 754, 372mAh g, respectively. -1 The whole battery has a capacity retention rate of 99.5% and a CE of about 100% after 100 cycles at 0.1 A / g, showing good cycling stability. These results indicate that carbon cloth@Fe3O4@Co-MOFs composites have a great background in the manufacture of high-capacity and high-stability lithium-ion batteries.

[0053] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modifications made within the spirit and principle of the present invention, etc.

Claims

1. A method for preparing a carbon cloth-loaded iron oxide material, characterized in that: The steps include: S1, soaking the carbon cloth in a nitric acid solution, taking it out, washing it and vacuum drying it to obtain a pretreated carbon cloth; S2, adding ferric chloride hexahydrate and sodium acetate to ethylene glycol, stirring and dissolving to obtain a mixed solution, transferring the mixed solution into a stainless steel autoclave lined with polytetrafluoroethylene, placing the pretreated carbon cloth and sealing, and hydrothermally reacting at 170-190° C. for 10-16 hours, taking out after completion, and washing to obtain a precursor; S3, soaking the precursor in a mixed solution of 2-methylimidazole and cobalt nitrate, taking it out after completion, cleaning it, vacuum drying it, and finally heating it to 400-600°C under argon protection for calcination to obtain a carbon cloth-loaded iron oxide material.

2. The method for preparing the carbon cloth-loaded iron oxide material according to claim 1, characterized in that: In step S1, the volume concentration of the nitric acid solution is 60%-70%.

3. The method for preparing the carbon cloth-loaded iron oxide material according to claim 1, characterized in that: In step S1, the vacuum drying temperature is 80°C.

4. The method for preparing the carbon cloth-loaded iron oxide material according to claim 1, characterized in that: In step S2, the molar ratio of ferric chloride hexahydrate to sodium acetate is 1:(2-2.5).

5. The method for preparing the carbon cloth-loaded iron oxide material according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 180° C. and the time is 12 h.

6. The method for preparing the carbon cloth-loaded iron oxide material according to claim 1, characterized in that: In step S3, the soaking temperature is 80-90°C and the soaking time is 10-15 hours.

7. The method for preparing the carbon cloth-loaded iron oxide material according to claim 1, characterized in that: In step S3, in the mixed solution of 2-methylimidazole and cobalt nitrate, the concentration of 2-methylimidazole is 4-6 mol / L, and the concentration of cobalt nitrate is 1-2 mol / L.

8. The method for preparing the carbon cloth-supported iron oxide material according to any one of claims 1 to 7, characterized in that: In step S3, the heating rate is 5°C / min, the calcination temperature is 500°C, and the calcination time is 2h.

9. Carbon cloth loaded iron oxide material prepared by the method according to any one of claims 1 to 8.

10. Use of the carbon cloth-loaded iron oxide material prepared by the method according to any one of claims 1 to 8 in preparing negative electrodes for lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of carbon cloth load nickel oxide coated iron oxide nanorod composite material

    CN106229153A

  • Synthesis method of Fe-MOF nano array loaded on carbon cloth

    CN109706739A

  • Preparation method of ferric oxide / CuCo-MOF / carbon cloth oxygen evolution composite electro-catalysis film

    CN113388860A

  • Preparation method and application of high-performance Fe2O3 negative electrode nanometer material

    CN114188164A

  • MOF-modified porous flexible self-supporting carbon paper and preparation method thereof

    CN116053411A